Code switching in the Malaysian ESL classroom: learners' attitudes and development of language proficiency / Nur Adibah Zamri - Zamri, Nur Adibah (2016)
Code switching has become a common phenomenon in Malaysian education context especially in the ESL classroom. It has also become the topic of debate among researchers, educators and policy makers. Some linguistic experts support the practice of code switching and some are against it. This research sought to investigate the use of code switching by teachers in ESL classroom and the learners' perceptions of teachers' code switching in the ESL classroom. In addition, it explored whether code switching practiced by teachers in the ESL classroom affected learners' attitudes and development of language proficiency. 113 students and four English teachers in a secondary school in Shah Alam were involved in this study. A survey and interviews were carried out to elicit the relevant data. Data from the study show that teachers apply code switching for certain purposes only. Mostly code switching was applied in weaker class. Moreover, teachers code switched in ESL classroom to make students understand the lesson, to develop good rapport, to develop students' confidence, to teach grammar and to control the classroom. In addition, it was also found that code switching has positive effects on learners' attitudes and it facilitates English learning among learners.